SIMBOL STATUS PETANI KAYA: PENGUASAAN LAHAN TEBU, BERHAJI, DAN PENDIDIKAN TINGGI - Ayu Musliha; Dika Ifanda Yunarko; Ma'rifatuzzayinah - (LPPM UNISDA, 2022)
Abstract This variety of qualitative phenomenological research raises specific topics about the social reality of the people of Rojopolo Village, Jatiroto District, and Lumajang Regency as an agricultural area with superior sugarcane commodities. Geographical, demographic, economic, social, and local cultural backgrounds are the center of the analysis. The period of data mining takes place from May 24 to 26, 2022 through observation, in-depth interviews, and documentation. The focus of the researcher narrows on the meaning of the status symbol of rich farmers (represented by the land owners), based on things of high value in the constellation of society, including land tenure as a symbol of wealth, pilgrimage as a symbol of religiosity, higher education as a symbol of position, to achieve comparisons. Life orientation between farming families/sugarcane land owners and farm laborers. Thus, researchers can conclude that the symbol always operates and builds a certain social status.